POFUT1 mRNA expression as an independent prognostic parameter in muscle-invasive bladder cancer - Wahby, Sarah; Jarczyk, Jonas; Fierek, Alexander; Heinkele, Jakob; Weis, Cleo-Aron Thias; Eckstein, Markus; Martini, Thomas; Porubský, Štefan; Hafner, Mathias; Erben, Philipp (Translational oncology, 2021)
Muscle-invasive bladder cancer (MIBC) is characterized by high recurrence and rapid progression. Progression is linked to changes in glycan structures and altered levels of glycosyltransferases. The relationship of mRNA expression by glycosyltransferase genes B4GALT1, EXT1, MGAT5B, and POFUT1 to the probability of surviving MIBC after radical cystectomy has not yet been investigated. mRNA expression was analyzed using qRT-PCR in formalin-fixed and paraffin-embedded tumor samples (n=105; 74% male patients and 26% female patients; median age=72years), correlated with histopathological variables, and evaluated by means of multivariable Cox regression analysis regarding to overall survival (OS), cancer-specific survival (CSS), and disease-free survival (DFS). Multivariable Cox regression analysis identified POFUT1 mRNA expression as superior prognostic marker, compared with currently used histological tumor stage methods, for CSS by MIBC patients following radical cystectomy. Thus, the patients with low POFUT1 mRNA were at a 4.9-fold greater risk for cancer-specific death according to the multivariable analysis (p=0.0001). Low mRNA levels predicted poor survival according to the Kaplan-Meier analysis ((POFUT1:OS p=0.0014; CSS p=0.0007; DFS p=0.0088); (EXT1:OS p=0.0150; CSS p=0.0130; DFS p=0.0286); (B4GALT1:CSS p=0.0134; DFS p=0.0493)). A subgroup analysis of patients without lymph node metastasis (pN−; n=73) indicated that low expression of POFUT1 predicted reduced OS (p=0.0073), CSS (p=0.0058,) and DSS (p=0.0079). Low levels of POFUT1 mRNA are an independent prognostic indicator for OS and CSS in MIBC patients following radical cystectomy. This finding demonstrates the importance of altered glycosylation for the progress of MIBC.